Peran Manajemen Sumber Daya Manusia Berkelanjutan dalam Membangun Organisasi Berkelanjutan Berbasis Sustainable Development Goals (SDGs) - Desvi Emti (Yayasan Almanar Pujud, 2026)
Organizational transformation towards sustainability requires changes in human resource management to align with the principles of the Sustainable Development Goals (SDGs). This study aims to analyze the role of Sustainable Human Resource Management (SRM) in building a sustainable organization based on the SDGs. The study uses a qualitative approach with a literature study method through the analysis of various scientific articles, books, and relevant academic sources. The results of the study indicate that Sustainable HRM has a strategic role in integrating economic, social, and environmental aspects into human resource management practices. The implementation of practices such as Green Human Resource Management, sustainable competency development, employee welfare, and the formation of an environmentally conscious organizational culture can increase employee engagement and support the achievement of the SDGs. Sustainable HRM is an important foundation in creating an organization that is adaptive, responsible, and capable of providing long-term value for all stakeholders.